Analisis Efektivitas Instalasi Pengolahan Air Limbah Dan Penilaian Masyarakat Terhadap Pengolahan Limbah Cair Rumah Sakit Umum W. Z. Yohanes Kupang - Waang, Delila Grez; Fernandez, Hironimus; Ramang, Ruslan (Bumi Lestari; Vol 16 No 2 (2016), 2016)
The hospital is one fairly large waste generators that produce adverse effects on the environment. This is because the waste has the potential to cause environmental and public health problems. Most hospital waste is a hazardous medical waste that is infectious. Research carried out in public hospitals WZ John Kupang showed fairly good efficiency. The WWTP used activated sludge have an efficiency of over 60% for all parameters and relatively efficient. The highest level of efficiency was the parameter of TSS (83.60%) and the lowest was the BOD (62.03%). However, the treatment of wastewater was classified not as effective with an average percentage of 60%, meaning that waste management which carried out was used all available resources but does not meet the expected target, or in other words sewage treatment efficient but not effective.
Keywords: hospital; waste treatment; environment; health